2005
DOI: 10.1107/s1744309105029246
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray characterization of the nitrile reductase QueF: a queuosine-biosynthesis enzyme

Abstract: QueF (MW = 19.4 kDa) is a recently characterized nitrile oxidoreductase which catalyzes the NADPH-dependent reduction of 7-cyano-7-deazaguanine (preQ 0 ) to 7-aminomethyl-7-deazaguanine, a late step in the biosynthesis of the modified tRNA nucleoside queuosine. Initial crystals of homododecameric Bacillus subtilis QueF diffracted poorly to 8.0 Å . A three-dimensional model based on homology with the tunnel-fold enzyme GTP cyclohydrolase I suggested catalysis at intersubunit interfaces and a potential role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Crystallization, X-ray Data Collection, and Crystal Structure Determination-Wild-type QueF and the single-site QueF mutant C55A from B. subtilis were overproduced and purified as described previously (13,14). For both the wild type and the C55A mutant, the enzyme⅐preQ 0 complex was crystallized at 293 K using the hanging drop method as described previously (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization, X-ray Data Collection, and Crystal Structure Determination-Wild-type QueF and the single-site QueF mutant C55A from B. subtilis were overproduced and purified as described previously (13,14). For both the wild type and the C55A mutant, the enzyme⅐preQ 0 complex was crystallized at 293 K using the hanging drop method as described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…For both the wild type and the C55A mutant, the enzyme⅐preQ 0 complex was crystallized at 293 K using the hanging drop method as described previously (13). Briefly, the enzyme (4 mg/ml in 100 mM Tris pH 7.5, 100 mM KCl) was mixed with preQ 0 at a 1:5-1:10 molar ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Escape of the imine from the active site into bulk solvent could lead to conversion to the observed aldehyde. Recent homology modeling (35) suggested that B. subtilis QueF is a homodecameric protein with active sites located at intersubunit interfaces. It is possible that the affinity tag that was used in our studies to facilitate purification of CinQ interferes with the native quaternary structure of this protein and leads to the diffusion of intermediates from the active site.…”
Section: Discussionmentioning
confidence: 99%
“…QueF catalyzes covalent attachment of this Cys thiolate sidechain to the carbon atom of the cyano group of preQ 0 to from a thioimide, which is converted to preQ 0 in two successive NADPH-dependent reactions [66]. Homology modeling [67] and crystallographic structure determinations have confirmed the structural similarities between QueF and GCH I, showing that it adopts a tunnel fold and the position of the catalytically essential cysteine residue [68]. …”
Section: Enzymes Involved In the Biosynthesis Of Deazapurinesmentioning
confidence: 99%